Aging-resistant high-performance polyurethane foam combination material and preparation method and application thereof

By using specific components and processes in the polyurethane foaming composite, low-density and high-performance polyurethane foaming composite is prepared, which solves the problems of high density and unstable product in cleaning of large pipes, and achieves aging resistance It has improved stain resistance and is suitable for cleaning of large pipe diameter pipes.

CN118812806BActive Publication Date: 2024-12-20SHANDONG INOV POLYURETHANE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411303318.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-20
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The existing polyurethane foaming combinations are high in density and heavy in cleaning of large pipe diameter pipes, which are inconvenient to use. Common methods to increase the amount of water or add 141B foaming agent will affect product performance and stability.

Method used

Aging-resistant high-performance polyurethane foaming combination composed of components A and components B by mass ratio of 100: (60-65), including polyester polyol, polymer polyol, foam stabilizer, methyl fluorosilicone oil, Hardening agent, catalyst and foaming agent are prepared by stirring and reaction, combining hydroxyfluorosilicone oil and microsphere foaming agent to reduce density and improve stain resistance and mechanical properties.

Benefits of technology

Prepare a polyurethane foaming combination material with low density, aging resistance, excellent mechanical properties and good stain resistance. It is suitable for cleaning of large pipe diameter pipes. The density can reach 103-110kg/m3, which extends the service life of the product and maintains the size. stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of polyurethane foam composite materials, and specifically relates to an aging-resistant high-performance polyurethane foam composite material and a preparation method and application thereof. The aging-resistant high-performance polyurethane foam composite material described in the present invention is made of component A and component B in a mass ratio of 100: (60-65), and component A includes the following raw materials: polyester polyol 1, polymer polyol, foam stabilizer, methyl fluorosilicone oil, hardener, catalyst, foaming agent 1, foaming agent 2; component B includes the following raw materials: polyester polyol 2, hydroxy fluorosilicone oil, toluene diisocyanate, liquefied MDI, and polymerization inhibitor. The aging-resistant high-performance polyurethane foam composite material provided by the present invention meets the needs of large-diameter pipeline cleaning, is applied to low-density pipeline cleaners, and has the advantages of low density, aging resistance, excellent mechanical properties, and good stain resistance. The present invention also provides a preparation method thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane foam composite materials, and in particular relates to an aging-resistant high-performance polyurethane foam composite material and a preparation method and application thereof. Background Art

[0002] Pipeline transportation is widely used due to its large capacity, low cost, safety and reliability, strong continuity, low energy consumption and high efficiency. However, its disadvantage is that as the transportation time increases, a large amount of dirt will adhere to the inner wall of the pipeline, increasing the resistance to transportation and causing problems in the transportation process. Therefore, it is very necessary to clean the inner wall of the pipeline.

[0003] At present, CN107501521A discloses a polyurethane foam composition used in pipe inner wall cleaners and its preparation method. It uses a variety of polyether polyols as raw materials. The prepared products have good elasticity and excellent hydrolysis resistance, but the mechanical properties of the products are poor. CN116655873A discloses a composite material for making a pipe cleaning head and its preparation method. By mixing polyester polyols and polyether polyols, a polyurethane composite material is prepared for use in pipe cleaning heads. The obtained product has good mechanical properties, especially wear resistance. In short, the polyurethane foam composite material has a good application effect in pipe cleaners, but the density of the pipe cleaners made by the above two patents is 200kg / m 3 The density is suitable for making medium-sized and smaller pipe cleaners. When making large-sized pipe cleaners, the weight is large, which is not conducive to practical use.

[0004] In order to reduce the density of the product and prepare a pipe cleaner suitable for large diameter pipes, the common method is to increase the amount of water or add some 141B foaming agent, but full water foaming affects the performance of the product, 141B foaming agent is highly polluting, and the products made by these two methods are easy to shrink, unstable in nature, and have poor use effects. Therefore, it is necessary to develop aging-resistant high-performance polyurethane foam combinations to meet the requirements of large diameter (Φ>1000mm) pipe cleaning. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art, provide an aging-resistant high-performance polyurethane foaming composite material, meet the needs of large-diameter pipeline cleaning, and apply it to a low-density pipeline cleaner, which has the advantages of low density, aging resistance, excellent mechanical properties, good stain resistance, etc. The present invention also provides a preparation method thereof.

[0006] The aging-resistant high-performance polyurethane foaming composite material of the present invention is composed of component A and component B in a mass ratio of 100:(60-65), wherein component A comprises the following raw materials in mass parts: 60-70 parts of polyester polyol 1, 30-40 parts of polymer polyol, 0.8-1.0 parts of foam stabilizer, 5.0-8.0 parts of methyl fluorosilicone oil, 5.0-7.0 parts of hardener, 0.8-1.0 parts of catalyst, 2.0-2.5 parts of foaming agent 1, and 10-15 parts of foaming agent 2;

[0007] Component B comprises the following raw materials and inhibitors in parts by weight: 20-30 parts of polyester polyol 2, 5-10 parts of hydroxy fluorosilicone oil, 50-55 parts of toluene diisocyanate, and 10-12 parts of liquefied MDI.

[0008] The polyester polyol 1 is a soft foam polyester polyol with a functionality of 2.5-3 and a hydroxyl value of 55-65 mgKOH / g, preferably PE-Y173 produced by Shandong Yinuowei Polyurethane Co., Ltd.

[0009] The polymer polyol has a solid content of 20-35wt.%, is grafted with styrene onto a basic polyester obtained by condensation of a small molecule diol and adipic acid, has a functionality of 2, and a number average molecular weight of 2000, and is preferably P-245T produced by Shandong Yinuowei Polyurethane Co., Ltd.

[0010] The polyester polyol 2 is prepared by esterification reaction of one or more of ethylene glycol, diethylene glycol or trimethylolpropane with adipic acid and terephthalic acid, with a hydroxyl value of 65-75 mgKOH / g, an acid value ≤0.5 mgKOH / g, a number average molecular weight of 1500-1800, and a functionality of 2. PE-2316 produced by Shandong Yinuowei Polyurethane Co., Ltd. is preferred.

[0011] The foam stabilizer is VORASURF™ HR 8835.

[0012] The methyl fluorosilicone oil is polymerized from fluorosilicone monomers, and its molecular chain ends are methyl-terminated organic silicon modified materials, preferably AFS-L-1011 produced by Shenzhen Guanheng New Material Technology Co., Ltd.

[0013] The hydroxy fluorosilicone oil is polymerized from fluorosilicone monomers, and the molecular chain ends thereof are organic silicon modified materials with hydroxyl groups, and AFS-L-1001 produced by Shenzhen Guanheng New Material Technology Co., Ltd. is preferred.

[0014] The hardener is a small molecule alcohol, and the small molecule alcohol is one or two of ethylene glycol and 1,4-butanediol.

[0015] The catalyst is a mixture of A33 and FOCAT-8003M, the mass ratio of A33 to FOCAT-8003M is 1:(0.25-0.5), A33 is a conventional commercial product, and FOCAT-8003M is a commercial product of Guangzhou Yourun Synthetic Materials Co., Ltd.

[0016] The foaming agent 1 is a chemical foaming agent: H2O.

[0017] The foaming agent 2 is a physical foaming agent: a microsphere foaming agent, preferably SA5000-D produced by Zhejiang Shuntai Rubber & Plastic Technology Co., Ltd., with a decomposition temperature of 148±4°C.

[0018] The toluene diisocyanate is a mixture of T80 and T65, and the mass ratio of T80 to T65 is (1:2)-(1:1).

[0019] The liquid MDI is MM103C.

[0020] The inhibitor is phosphoric acid, and the dosage is 40ppm.

[0021] The method for preparing the aging-resistant high-performance polyurethane foaming composite material comprises the following steps:

[0022] (1) Preparation of component A: polyester polyol 1, polymer polyol, foam stabilizer, methyl fluorosilicone oil, hardener, catalyst, foaming agent 1 and foaming agent 2 are mixed at room temperature and stirred evenly to obtain component A;

[0023] (2) Preparation of component B: Start stirring and control the frequency to 43-47 Hz, add hydroxy fluorosilicone oil and polymerization inhibitor to polyester polyol 2, mix, add toluene diisocyanate, raise the temperature to 75-80°C for reaction, add liquefied MDI, stir, and obtain component B;

[0024] (3) Component A and component B are mixed according to a mass ratio, injected into a mold, and after ripening, an aging-resistant high-performance polyurethane foam composite material is obtained.

[0025] Application of the aging-resistant high-performance polyurethane foam combination material: using it in a low-density pipe cleaner.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The aging-resistant high-performance polyurethane foaming composite material of the present invention introduces methyl fluorosilicone oil into component A and hydroxy fluorosilicone oil into component B, thereby improving the stain resistance of the product; at the same time, the strong hydrophobicity of fluorine atoms is utilized to slow down the problems of product powdering and cracking caused by hydrolysis, thereby extending the service life of the product.

[0028] (2) The aging-resistant high-performance polyurethane foaming composite material of the present invention has water and microsphere foaming agent as the foaming agents. Under the premise of meeting the foaming ratio, the introduction of the microsphere foaming agent reduces the amount of water used, avoids the generation of excessive urea groups that affect product performance, and the size retention rate can reach 93%. The decomposition temperature of the microsphere foaming agent is 148±4°C, and the temperature generated by the foaming itself can reach above 150°C, which is sufficient to stimulate the activation of the microsphere foaming agent.

[0029] (3) The aging-resistant high-performance polyurethane foaming composite material of the present invention uses a mixture of A33 and FOCAT-8003M as a catalyst, which increases the surface thickness of the product and also enhances the mechanical properties, hydrophobicity and stain resistance of the product.

[0030] (4) The pipeline cleaner prepared by the aging-resistant high-performance polyurethane foam composite material of the present invention can reach a density of 103-110kg / m 3 , which meets the needs of cleaning large-diameter pipelines, and the preparation method is simple. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with specific embodiments.

[0032] The raw materials used in the examples, unless otherwise specified, are commercially available conventional raw materials.

[0033] Some of the raw materials used in the examples and comparative examples are described as follows:

[0034] PE-Y173: produced by Shandong Yinuowei Polyurethane Co., Ltd.

[0035] P-245T: produced by Shandong Yinuowei Polyurethane Co., Ltd.

[0036] VORASURF™ HR 8835: produced by Dow Chemical (Shanghai) Co., Ltd.;

[0037] AFS-L-1011: produced by Shenzhen Guanheng New Material Technology Co., Ltd.;

[0038] FOCAT-8003M: produced by Guangzhou Yourun Synthetic Materials Co., Ltd.

[0039] SA5000-D: produced by Zhejiang Shuntai Rubber & Plastic Technology Co., Ltd.

[0040] PE-2316: produced by Shandong Yinuowei Polyurethane Co., Ltd.;

[0041] AFS-L-1001: produced by Shenzhen Guanheng New Material Technology Co., Ltd.;

[0042] T80 and T65 mixture: produced by Wanhua Chemical Group Co., Ltd.

[0043] MM103C: Produced by BASF SE.

[0044] The method for preparing the aging-resistant high-performance polyurethane foaming composite material of the present invention comprises the following steps:

[0045] (1) Preparation of Component A: Component A comprises the following raw materials in parts by weight: 60-70 parts of polyester polyol 1, 30-40 parts of polymer polyol, 0.8-1.0 parts of foam stabilizer, 5.0-8.0 parts of methyl fluorosilicone oil, 5.0-7.0 parts of hardener, 0.8-1.0 parts of catalyst, 2.0-2.5 parts of foaming agent 1, and 10-15 parts of foaming agent 2;

[0046] Mix the above raw materials at room temperature, stir at a frequency of 45±2Hz, and stir evenly to obtain component A;

[0047] (2) Preparation of component B: Component B includes the following raw materials and phosphoric acid in parts by weight: 20-30 parts of polyester polyol 2, 5-10 parts of hydroxy fluorosilicone oil, 50-55 parts of toluene diisocyanate, and 10-12 parts of liquefied MDI;

[0048] The reactor was replaced with nitrogen, polyester polyol 2 (water content ≤ 0.05%) was added, stirring was started, the stirring frequency was 45±2Hz, hydroxy fluorosilicone oil and 40ppm phosphoric acid were added, stirring was continued for 10min, toluene diisocyanate was added, the temperature was raised to 77.5±2.5℃, the temperature was kept for 2.5min, liquefied MDI at a temperature not higher than 50℃ was added, stirring was continued for 15min, and component B was obtained;

[0049] (3) Component A and component B are mixed in a mass ratio of 100:(60-65), injected into a mold, and after ripening, an aging-resistant high-performance polyurethane foam composite material is obtained.

[0050] Example 1

[0051] The method for preparing the aging-resistant high-performance polyurethane foaming composite material comprises the following steps:

[0052] (1) Preparation of Component A: Component A includes the following raw materials in parts by weight: 60 parts of PE-Y173, 40 parts of P-245T, 0.8 parts of VORASURF™ HR 8835, 5.0 parts of AFS-L-1011, 7.0 parts of ethylene glycol, 0.8 parts of A33:FOCAT-8003M=1:0.5, 2.0 parts of H2O, and 15 parts of SA5000-D;

[0053] Mix the above raw materials at room temperature, stir at a frequency of 45±2Hz, and stir evenly to obtain component A;

[0054] (2) Preparation of component B: Component B includes the following raw materials and phosphoric acid in the following weight proportions: 20 parts of PE-2316, 10 parts of AFS-L-1001, 50 parts of toluene diisocyanate (T80:T65=1:2), and 10 parts of MM103C;

[0055] The reactor was purged with nitrogen, and PE-2316 (water content ≤ 0.05%) was added. Stirring was started at a frequency of 45±2Hz. AFS-L-1001 and 40ppm phosphoric acid were added. Stirring was performed for 10min. Toluene diisocyanate (T80:T65=1:2) was added. The temperature was raised to 77.5±2.5℃, and the temperature was kept for 2.5min. The temperature was then added to MM103C not higher than 50℃, and stirred for 15min to obtain component B.

[0056] (3) Component A and component B are mixed in a mass ratio of 100:65, injected into a mold, and cured for 7 minutes to obtain an aging-resistant high-performance polyurethane foam composite material.

[0057] Example 2

[0058] The method for preparing the aging-resistant high-performance polyurethane foaming composite material comprises the following steps:

[0059] (1) Preparation of Component A: Component A includes the following raw materials in parts by weight: 70 parts of PE-Y173, 30 parts of P-245T, 1.0 parts of VORASURF™ HR 8835, 6.0 parts of AFS-L-1011, 6.0 parts of ethylene glycol, 1.0 parts of A33:FOCAT-8003M=1:0.5, 2.5 parts of H2O, and 10 parts of SA5000-D;

[0060] Mix the above raw materials at room temperature, stir at a frequency of 45±2Hz, and stir evenly to obtain component A;

[0061] (2) Preparation of component B: Component B includes the following raw materials and phosphoric acid in the following weight proportions: 30 parts of PE-2316, 5 parts of AFS-L-1001, 50 parts of toluene diisocyanate (T80:T65=1:2), and 10 parts of MM103C;

[0062] The reactor was purged with nitrogen, and PE-2316 (water content ≤ 0.05%) was added. Stirring was started at a frequency of 45±2Hz. AFS-L-1001 and 40ppm phosphoric acid were added. Stirring was performed for 10min. Toluene diisocyanate (T80:T65=1:2) was added. The temperature was raised to 77.5±2.5℃, and the temperature was kept for 2.5min. The temperature was then added to MM103C not higher than 50℃, and stirred for 15min to obtain component B.

[0063] (3) Component A and component B are mixed in a mass ratio of 100:60, injected into a mold, and cured for 7 minutes to obtain an aging-resistant high-performance polyurethane foam composite material.

[0064] Example 3

[0065] The method for preparing the aging-resistant high-performance polyurethane foaming composite material comprises the following steps:

[0066] (1) Preparation of Component A: Component A includes the following raw materials in parts by weight: 65 parts of PE-Y173, 35 parts of P-245T, 0.8 parts of VORASURF™ HR 8835, 8.0 parts of AFS-L-1011, 7.0 parts of ethylene glycol, 0.9 parts of A33:FOCAT-8003M=1:0.5, 2.2 parts of H2O, and 13 parts of SA5000-D;

[0067] Mix the above raw materials at room temperature, stir at a frequency of 45±2Hz, and stir evenly to obtain component A;

[0068] (2) Preparation of component B: Component B includes the following raw materials and phosphoric acid in the following weight proportions: 25 parts of PE-2316, 10 parts of AFS-L-1001, 55 parts of toluene diisocyanate (T80:T65=1:1.5), and 10 parts of MM103C;

[0069] The reactor was replaced with nitrogen, and PE-2316 (water content ≤ 0.05%) was added. Stirring was started at a frequency of 45±2Hz. AFS-L-1001 and 40ppm phosphoric acid were added. Stirring was performed for 10min. Toluene diisocyanate (T80:T65=1:1.5) was added. The temperature was raised to 77.5±2.5℃, and the temperature was kept for 2.5min. The temperature was then added to MM103C not higher than 50℃, and stirred for 15min to obtain component B.

[0070] (3) Component A and component B are mixed in a mass ratio of 100:62, injected into a mold, and cured for 7 minutes to obtain an aging-resistant high-performance polyurethane foam composite material.

[0071] Example 4

[0072] The method for preparing the aging-resistant high-performance polyurethane foaming composite material comprises the following steps:

[0073] (1) Preparation of Component A: Component A includes the following raw materials in parts by weight: 60 parts of PE-Y173, 40 parts of P-245T, 1.0 parts of VORASURF™ HR 8835, 8.0 parts of AFS-L-1011, 5.0 parts of ethylene glycol, 0.8 parts of A33:FOCAT-8003M=1:0.5, 2.5 parts of H2O, and 12 parts of SA5000-D;

[0074] Mix the above raw materials at room temperature, stir at a frequency of 45±2Hz, and stir evenly to obtain component A;

[0075] (2) Preparation of component B: Component B includes the following raw materials and phosphoric acid in the following weight proportions: 25 parts of PE-2316, 7 parts of AFS-L-1001, 53 parts of toluene diisocyanate (T80:T65=1:2), and 12 parts of MM103C;

[0076] The reactor was purged with nitrogen, and PE-2316 (water content ≤ 0.05%) was added. Stirring was started at a frequency of 45±2Hz. AFS-L-1001 and 40ppm phosphoric acid were added. Stirring was performed for 10min. Toluene diisocyanate (T80:T65=1:2) was added. The temperature was raised to 77.5±2.5℃, and the temperature was kept for 2.5min. The temperature was then added to MM103C not higher than 50℃, and stirred for 15min to obtain component B.

[0077] (3) Component A and component B are mixed in a mass ratio of 100:62, injected into a mold, and cured for 7 minutes to obtain an aging-resistant high-performance polyurethane foam composite material.

[0078] Example 5

[0079] The method for preparing the aging-resistant high-performance polyurethane foaming composite material comprises the following steps:

[0080] (1) Preparation of Component A: Component A includes the following raw materials in parts by weight: 70 parts of PE-Y173, 30 parts of P-245T, 0.9 parts of VORASURF™ HR 8835, 7.0 parts of AFS-L-1011, 5.0 parts of 1,4-butanediol, 1.0 parts of A33:FOCAT-8003M=1:0.25, 2.3 parts of H2O, and 15 parts of SA5000-D;

[0081] Mix the above raw materials at room temperature, stir at a frequency of 45±2Hz, and stir evenly to obtain component A;

[0082] (2) Preparation of component B: Component B includes the following raw materials and phosphoric acid in the following weight proportions: 20 parts of PE-2316, 10 parts of AFS-L-1001, 50 parts of toluene diisocyanate (T80:T65=1:1), and 10 parts of MM103C;

[0083] The reactor was purged with nitrogen, and PE-2316 (water content ≤ 0.05%) was added. Stirring was started at a frequency of 45±2Hz. AFS-L-1001 and 40ppm phosphoric acid were added. Stirring was performed for 10min. Toluene diisocyanate (T80:T65=1:1) was added. The temperature was raised to 77.5±2.5℃, and the temperature was kept for 2.5min. The temperature was then added to MM103C at a temperature not higher than 50℃, and stirred for 15min to obtain component B.

[0084] (3) Component A and component B are mixed in a mass ratio of 100:62, injected into a mold, and cured for 7 minutes to obtain an aging-resistant high-performance polyurethane foam composite material.

[0085] Comparative Example 1

[0086] This comparative example is the same as Example 1, except that AFS-L-1011 in component A is replaced with an equal amount of PE-Y173, and the remaining steps are the same.

[0087] Comparative Example 2

[0088] This comparative example is the same as Example 1, except that AFS-L-1001 in component B is replaced by an equal amount of PE-2316, and the remaining steps are the same.

[0089] Comparative Example 3

[0090] This comparative example is the same as Example 2, except that 10 parts of SA5000-D in component A are removed, the mass fraction of H2O is increased from 2.5 parts to 3.5 parts, and the remaining steps are the same.

[0091] Comparative Example 4

[0092] This comparative example is the same as Example 3, except that the mixture of A33:FOCAT-8003M=1:0.5 in component A is replaced with an equal amount of A33, and the remaining steps are the same.

[0093] The performance of the aging-resistant high-performance polyurethane foam composite materials prepared in Examples 1-5 and Comparative Examples 1-4 was tested. The test results are shown in Table 1.

[0094] Hardness and tear strength were tested according to GB / T 2411-2008 and GB / T 10808-2006 respectively, and the test standard for tensile strength and elongation was GB / T 6344-2008; the dimensional retention rate was tested according to the standard GB / T 10801.2-2018, dimensional retention rate (%) = product volume after use / product volume at mold opening × 100%, the higher the dimensional retention rate, the more stable the product is, the less likely it is to deform, and the practicality of the product is maintained; the water contact angle was tested using the method in ASTM D7490-2013; the aging test conditions were: temperature 80°C, relative humidity 80%, left for 48 hours, and the tensile strength change rate and elongation change rate of the product were tested after aging; the pollution resistance test was to mix edible oil and dark soy sauce in a mass ratio of 5:2, immerse the product in it for 10 minutes, bake it in an oven at 60°C for 30 minutes, and then wash it in clean water to measure the color difference on the surface of the product.

[0095] Table 1 Test results

[0096]

[0097] It can be seen from the test results of Examples 1-5 and Comparative Examples 1-4 in Table 1 that, compared with Comparative Examples 1 and 2, the product in Example 1 has a larger water contact angle, a smaller change in elongation and tensile strength after aging, and a better stain resistance test effect, which indicates that the addition of methyl fluorosilicone oil and hydroxy fluorosilicone oil improves the stain resistance and hydrophobicity of the product, and the strong hydrophobicity of fluorine atoms slows down the aging of the product and extends the service life of the product; secondly, Comparative Examples 1 and 2 further show that when AFS-L-1011 and AFS-L-1001 exist at the same time, the stain resistance and anti-aging performance of the product are better, and the two fluorosilicone oils work together to enhance the performance of the product.

[0098] Compared with Example 2, Comparative Example 3 uses water instead of the physical foaming agent SA5000-D to produce a product with lower density, but the mechanical properties of the product are significantly reduced; at the same time, the product made by the all-water system has a low dimensional retention rate and unstable properties. Combined with the test results of Example 2, it is shown that adding an appropriate amount of physical foaming agent can increase the stability of the product and improve the life of the product.

[0099] Compared with Comparative Example 4, Example 3 uses a mixture of A33 and FOCAT-8003M as a catalyst, which is beneficial to increase the surface thickness of the product. At the same time, the thicker skin is also beneficial to improving the mechanical properties, hydrophobicity and stain resistance of the product.

Claims

1. An aging-resistant high-performance polyurethane foam composition, characterized in that: The invention is composed of component A and component B in a mass ratio of 100:(60-65), wherein component A includes the following raw materials in mass parts: 60-70 parts of polyester polyol 1, 30-40 parts of polymer polyol, 0.8-1.0 parts of foam stabilizer, 5.0-8.0 parts of methyl fluorosilicone oil, 5.0-7.0 parts of hardener, 0.8-1.0 parts of catalyst, 2.0-2.5 parts of foaming agent 1, and 10-15 parts of foaming agent 2; Component B includes the following raw materials and inhibitors in parts by weight: 20-30 parts of polyester polyol 2, 5-10 parts of hydroxy fluorosilicone oil, 50-55 parts of toluene diisocyanate, and 10-12 parts of liquefied MDI; The polyester polyol 1 is a soft foam polyester polyol with a functionality of 2.5-3 and a hydroxyl value of 55-65 mgKOH / g; The polymer polyol has a solid content of 20-35wt.%, and is grafted with styrene onto a base polyester obtained by condensation of a small molecule diol and adipic acid, has a functionality of 2, and a number average molecular weight of 2000; The polyester polyol 2 is prepared by esterification reaction of one or more of ethylene glycol, diethylene glycol, trimethylolpropane with adipic acid and terephthalic acid, and has a hydroxyl value of 65-75 mgKOH / g, an acid value of ≤0.5 mgKOH / g, a number average molecular weight of 1500-1800, and a functionality of 2; The catalyst is a mixture of A33 and FOCAT-8003M; The foaming agent 1 is a chemical foaming agent, and the chemical foaming agent is water; The foaming agent 2 is a physical foaming agent, which is a microsphere foaming agent with a decomposition temperature of 148±4°C; The hardener is a small molecule alcohol, and the small molecule alcohol is one or two of ethylene glycol and 1,4-butanediol.

2. The aging-resistant high-performance polyurethane foam composition according to claim 1, characterized in that: The foam stabilizer is VORASURF™ HR 8835.

3. The aging-resistant high-performance polyurethane foam composition according to claim 1, characterized in that: The methyl fluorosilicone oil is polymerized from fluorosilicone monomers, and the molecular chain ends of the methyl fluorosilicone oil are organic silicon modified materials terminated with methyl groups.

4. The aging-resistant high-performance polyurethane foam composition according to claim 1, characterized in that: The hydroxy fluorosilicone oil is polymerized from fluorosilicone monomers, and the molecular chain ends of the hydroxyl-containing organic silicon modified materials.

5. The aging-resistant high-performance polyurethane foam composition according to claim 1, characterized in that: The mass ratio of the mixture of A33 and FOCAT-8003M is 1:(0.25-0.5).

6. The aging-resistant high-performance polyurethane foam composition according to claim 1, characterized in that: The toluene diisocyanate is a mixture of T80 and T65, and the mass ratio of T80 to T65 is (1:2)-(1:1).

7. The aging-resistant high-performance polyurethane foam composition according to claim 1, characterized in that: The liquefied MDI is MM103C; the inhibitor is phosphoric acid.

8. A method for preparing the aging-resistant high-performance polyurethane foaming composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Preparation of component A: polyester polyol 1, polymer polyol, foam stabilizer, methyl fluorosilicone oil, hardener, catalyst, foaming agent 1 and foaming agent 2 are mixed at room temperature and stirred evenly to obtain component A; (2) Preparation of component B: Start stirring and control the frequency to 43-47 Hz, add hydroxy fluorosilicone oil and polymerization inhibitor to polyester polyol 2, mix, add toluene diisocyanate, raise the temperature to 75-80°C for reaction, add liquefied MDI, stir, and obtain component B; (3) Component A and component B are mixed according to the mass ratio, injected into a mold, and after ripening, an aging-resistant high-performance polyurethane foam composite material is obtained.

9. An application of the aging-resistant high-performance polyurethane foaming composition according to any one of claims 1 to 7, characterized in that: Use it for low density pipe cleaners.

Citation Information

Patent Citations

  • Polyurethane foam composition applied to pipeline inner wall cleaning device and preparation method thereof

    CN107501521A

  • Self-skinning compound material for heat-resistant polyurethane foaming tyre and preparation method thereof

    CN105001394A

  • Composite material for manufacturing pipeline cleaning head and preparation method of composite material

    CN116655873A